2007
DOI: 10.1371/journal.pone.0001339
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of the Ligands for the Natural Killer Cell Receptors NKp30 and NKp44

Abstract: BackgroundThe natural cytotoxicity receptors (NCR) are important to stimulate the activity of Natural Killer (NK) cells against transformed cells. Identification of NCR ligands and their level of expression on normal and neoplastic cells has important implications for the rational design of immunotherapy strategies for cancer.Methodology/Principal FindingsHere we analyze the expression of NKp30 ligand and NKp44 ligand on 30 transformed or non-transformed cell lines of different origin. We find intracellular an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 39 publications
(43 reference statements)
3
84
0
Order By: Relevance
“…The family of NCRs comprises three members, NKp30, NKp44 and NKp46 all of which are involved in the killing of tumor cells. 4,5 NKp30 belongs to the CD28 family and is expressed on the majority of NK cells. 2 It is not only involved in tumor cell lysis but also in the interaction with dendritic cells.…”
Section: Introductionmentioning
confidence: 99%
“…The family of NCRs comprises three members, NKp30, NKp44 and NKp46 all of which are involved in the killing of tumor cells. 4,5 NKp30 belongs to the CD28 family and is expressed on the majority of NK cells. 2 It is not only involved in tumor cell lysis but also in the interaction with dendritic cells.…”
Section: Introductionmentioning
confidence: 99%
“…NKp30 promotes independently or together with other stimulatory receptors the recognition and killing of tumor cells by NK cells (8,12). NKp30-specific ligands are expressed on different types of tumors that have been demonstrated to be lysed by NK cells in an NKp30-dependent manner (8,(12)(13)(14)(15). Ligation of NKp30, moreover, has been shown to trigger the release of immunostimulatory cytokines such as TNF-a and IFN-g (16,17).…”
mentioning
confidence: 99%
“…Although K562 cells do not carry HLA-E, it was proposed by Figueiredo. et al that this increased cytolytic activity is partially mediated by the natural cytotoxicity receptor NKp30 (Figueiredo, Settsam, & Blasczyk, 2009) since it was recently shown that the ligand of NKp30 is expressed in K562 cells (Byrd, Hoffmann, Jarahian, Momburg, & Watzl, 2007). In general, the stroma was a more potent inducer for cord blood differentiation into functional NK cells than the other experimental conditions.…”
Section: Differentiation Of Natural Killer Cells From Human Umbilicalmentioning
confidence: 97%